2006
DOI: 10.1111/j.1750-3841.2006.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Flavonoids on Cell Proliferation in Hepa‐1c1c7 and LNCaP Cancer Cell Lines

Abstract: Fruits and vegetables contain a variety of phytochemicals, including flavonoids, which have antioxidant and anticancer properties. The purpose of this study was to evaluate the antiproliferative effects and synergistic interactions of a variety of flavonoids in Hepa‐1c1c7, a mouse liver cancer cell line, and LNCaP, a human prostate cancer cell line. Aglycone flavonoids, such as quercetin, kaempferol, and naringenin (at 12.5 to 50 μM), inhibited cancer cell proliferation in both cell lines in a dose dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…It is interesting the kaempferol glucoside exhibited moderate cytotoxicity compared to other kaempferol and its structurally related flavones reported in the literature (Dimas et al, 2000;Gardenia Carmem et al, 2005;Nakamura et al, 2005), but dramatically antiproliferative effects, coordinate results are also available. Campbell et al (2006) reported that kaempferol (at 12.5-50 M) significantly inhibited mouse liver cancer cell line Hepa-1c1c7 and LNCaP, a human prostate cancer cell proliferation in a dose-dependent manner without cytotoxicity. Kaempferol significantly inhibited platelet-derived growth factor (PDGF)-BB-induced proliferation and without any cytotoxicity in primary cultured rat aortic vascular smooth muscle cells (VSMCs) (Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting the kaempferol glucoside exhibited moderate cytotoxicity compared to other kaempferol and its structurally related flavones reported in the literature (Dimas et al, 2000;Gardenia Carmem et al, 2005;Nakamura et al, 2005), but dramatically antiproliferative effects, coordinate results are also available. Campbell et al (2006) reported that kaempferol (at 12.5-50 M) significantly inhibited mouse liver cancer cell line Hepa-1c1c7 and LNCaP, a human prostate cancer cell proliferation in a dose-dependent manner without cytotoxicity. Kaempferol significantly inhibited platelet-derived growth factor (PDGF)-BB-induced proliferation and without any cytotoxicity in primary cultured rat aortic vascular smooth muscle cells (VSMCs) (Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical screening considers that every compound, regardless of their proportion in the plant, known or not, may be an active ingredient [39]. Studies suggest that combinations of phenolics naturally present in fruits and vegetables as a whole inhibit cancer cell growth more effectively than the individual compounds [40]. …”
Section: Discussionmentioning
confidence: 99%
“…These anthraquinone derivatives are well known to exhibit a variety of biological activities [19], such as antimicrobial [2], antifungal [20], antitumor [21], antioxidant [22], cytotoxic [23], and hypoglycemic [24] activities. The flavonoid kaempferol has been reported to have anticancer properties [25,26]. It is clear that there is a correlation between the ethnopharmacological properties ascribed to this herbal medicine and the biological activities of these phenolic compounds.…”
Section: Published In Final Edited Form Asmentioning
confidence: 99%